Large Infaunal Bivalves Determine Community Uptake of Macroalgal Detritus and Food Web Pathways - Agnes M. L. Karlson; Conrad A. Pilditch; P. Keith Probert; Daniel Leduc; Candida Savage (Ecosystems, 2021)
Human activities alter biodiversity, influencing bottom-up and top-down control on food webs which can affect ecosystem functioning. In marine ecosystems, large bivalves play a critical role in benthic–pelagic coupling including nutrient cycling; however, their influence on the uptake of detrital organic matter by benthic communities is less understood. In a replicated factorial field experiment, we examined how the presence or absence (overharvesting scenario) of a large suspension-feeding clam on an intertidal sandflat and the addition of isotopically enriched macroalgal ( Ulva sp.) detritus (eutrophication scenario) influenced infaunal biodiversity, and how changes in trophic interactions influenced key ecosystem functions (nutrient cycling and benthic metabolism and primary production). Both clams and Ulva increased community metabolism, but only clams had an effect on nutrient regeneration. We used the 13 C- and 15 N-enriched Ulva to quantify the effect of clams on detritus uptake in fauna and recovery in sediment. Due to their large biomass, nitrogen incorporation by clams constituted one-third of the infaunal community uptake after 14 days. Clam uptake likely resulted from ingestion of resuspended microphytobentos which had utilized 15 N leaking out from decomposing Ulva . In plots without Ulva addition, the effect of clams on the overall resource utilization by the benthic community using natural abundance isotope niche metrics were tested. In plots without clams, the isotope niche of the community was reduced, and less carbon of pelagic origin was channelled into the infaunal food web. Our results imply that the loss of clams changes trophic pathways and reduces community uptake of macroalgal detritus, potentially exacerbating eutrophication. Graphic Abstract